Innovation of Evaluation of Plating Dance Learning for High School Students Based on “Find the Match” - Putri Ajeng Wulan Julitasari; Agus Cahyono; Syahrul Syah Sinaga; Wahyu Lestari (Edumaspul: Jurnal Pendidikan, 2024)
Evaluation innovation in art learning using digital media is very necessary. In the era of digitalization development, teachers must have skills in designing and using innovative learning media to attract students' interest. Through evaluating learning innovations using the WorldWall "Find The Match" application in SMA in learning plate dance, students' creativity and interest in learning increase as well as cognitive traits. in developing students. The purpose of this study is to create an evaluation tool using the Wordwall application "Find The Match" to meet the needs of students in the digitalization era by learning plate dance. The research method uses qualitative data Research and Development (RnD) research with descriptive percentage analysis. The results of the study using the wordwall application "find the match" in learning plate dance for high school students and art and culture teachers were very effective and practical which was used in the title "West Sumatra Plate Dance". Using learning through the application makes students' interest in learning dance increase as evidenced by the excellent student response and stimulates students' cognitive development. Keywords: Dance Learning, Evaluation Innovation, Wordwall "Find The Match", Plate Dance.